PENINGKATAN HASIL BELAJAR PKn MENGGUNAKAN MODEL PEMBELEJARAN KOOPERATIF INSIDE-OUTSIDE CIRCLE PADA PESERTA DIDIK KELAS V SDN. - Luncana Faridhoh Sasmito (JURNAL MITRA SWARA GANESHA, 2015)
ABSTRACT This study aims to: (1) To improve learning outcomes Civics using cooperative learning model inside out side the circle on the learner class V SDN.This research is a classroom action research that shows the flow of research include four stages, starting from planning, implementation, observation, and reflection. The four stages of a cycle. The study took place in two cycles. Data collection techniques in this study is the observation, testing and documentation. Data analysis technique used is an interactive model, the relationship between the three components include: data reduction, data presentation, and conclusion or verification. Based on the results of this study concluded that the use of cooperative learning model inside out side the circle can improve learning outcomes Civics class student V SDN. Evidenced by the growing student learning outcomes before and after implementation of the action. At the time of the pre-action value by an average of 69.92 in the first cycle increased to 72.58, and the second cycle increased to 88.92. As for the percentage of students according to criteria completeness Complete Minimal (KKM) is 70, when the pre-action students who completed a total of 12 students or 38.71% of the total number of 31 students. In the first cycle the percentage of completeness showed an increase of 16.12% from students who completed a total of 12 students or 38.71% at the time of pre-action, increasing to 17 students or 54.83% during the first cycle of the total number of 31 students. In the second cycle the percentage of completeness again showed an increase of 41.94%, that of the students who completed a total of 17 students or 54.83% during the first cycle, increased to 30 students or 96.77% during the second cycle of the total number of 31 students , Keywords: inside out side the circle, Freedom to Organize.